If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6 + x = 3x + -31 Reorder the terms: 6 + x + x = 3x + -31 Combine like terms: x + x = 2x 6 + 2x = 3x + -31 Reorder the terms: 6 + 2x = -31 + 3x Solving 6 + 2x = -31 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 2x + -3x = -31 + 3x + -3x Combine like terms: 2x + -3x = -1x 6 + -1x = -31 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -1x = -31 + 0 6 + -1x = -31 Add '-6' to each side of the equation. 6 + -6 + -1x = -31 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = -31 + -6 -1x = -31 + -6 Combine like terms: -31 + -6 = -37 -1x = -37 Divide each side by '-1'. x = 37 Simplifying x = 37
| 6x+45+75=180 | | -8x-31=3(8+3x) | | 2(4n-2)=36-2n | | 3x-6=-27 | | (3*n)+4=32 | | 5(2+3w)-1=6 | | 48x^2+12x-90=0 | | x=0.8x+4 | | x=0.8+4 | | 3x-9=23-5x | | 3=-2/3*3+3 | | 5p-2=32 | | 2x-1+2x-1+2x-1= | | y^2+y=12 | | 5x*10=100 | | 9=7m+1-6 | | 2x*3=5 | | 3-(3t+4)=t | | 13x+436=17x | | 35E-7=0 | | 26=15(5-d) | | 18r+9=-5.7r-6 | | 6x^2+6x-16=0 | | 2.3-4.1= | | 4-t+5=t-19 | | 8.2p-33.4=1.7-3.5p | | 12(x-8)=-8-4 | | 1r+3r-5r=6+2 | | 0+91= | | 2x+(30-5x)=90 | | -36=6(-2x+2) | | 480=30d |